Contributing traditional class communication culture of Arabic language teaching at Pesantren to higher English education classroom in Indonesian contexts - Endah Nur Tjendani; Imam Ghozali; Mohammad Iqbal Muhajir (Universitas Muhammadiyah Malang, 2025)
Classroom communication has a prominent role in teaching learning in traditional and modern class, so this research aimed to explore the contribution of Arabic traditional class communication culture to higher English education in Indonesian contexts. This research applied qualitative method with data collection using in-depth observation, interview, and document to the cultural dynamics within university and Pesantren classrooms. All data had been analyzed using themes, namely teachers’ notion, student’s activities, and classroom organization pattern. The findings shown that 1) teacher contributed to the knowledge symbol, to have moral character as a model, and to be strict and fair, and donated to class activities, like reading aloud, memorizing, formal examination, giving speech, mush explanations, and teacher-centered; 2) students came up with a knowledge receiver, depend on teachers’ instruction, strong memorization, exam performance, but a little critical thinking shown by written task/project, and 3) class organization provided by Sorogan, Setoran, Muhādaṡah Yaumiyyah, Muhāḍarah/Dakwah, and dialogue in Muadakaroh/Bathsul Masa'il, like reading aloud individual or together with good or proper pronunciation on every phrase, explaining or memorizing grammatical and vocabulary with its detailed meanings, and apply hundreds words and grammatical in various exercises, rearranging jumbled sentences, memorizing, and the other technique, translating on word to word, sentence to sentence, texts to texts, and texts to contexts reported in written or oral, and speaking in form of speech, preach, discussion, monolog, and conversation. But, the similar findings existed in memorization and speech carried out both in Islamic boarding school classes and higher education. So, it is recommended for further research how the pesantren method is applied to further improve critical thinking